The Implementation of Google Classroom Application in Teaching and Learning Process at Ninth Grade Students At SMP Negeri 4 Tejakula - widya Ketut Widya Astuti (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
This study aims to determine 1) how the implementation of Google Classroom in the teaching and learning process of English in grade 9 SMP Negeri 4 Tejakula and 2) the perceptions of grade 9 students of SMP Negeri 4 Tejakula on the use of Google Classroom in the learning and teaching process of English. This study uses a mixed-method. The subjects of this study were two English teachers in grade 9 and grade 9 students from class 9A, 9B, 9C, 9D, 9E, 9F, 9G, and 9H. The object of this research is the implementation of the Google Classroom in the learning and teaching process of English in grade 9 at SMP Negeri 4 Tejakula and the perceptions of the 9th-grade students of SMP Negeri 4 Tejakula on the use of Google Classroom in the learning and teaching process collected by the method of observation and questionnaires. From the research conducted on teachers and all students in grade 9 shows that, based on the results of observations, teachers use Google Classroom as a media for sending and receiving assignments or tests, while the results of questionnaires related to student perceptions indicate that the implementation of Google Classroom in the process of language learning and teaching English in grade 9 showed a positive response. This is indicated by the mean score of 3.20. From this mean score, it can be concluded that most of the students agreed with the statement contained in the questionnaire so that they were able to get the mean score which occupied the "positive" criteria.